Hegemoni Ideologi Feodalistis dalam Karya Sastra Berlatar Sosiokultural Bali - I Kadek Adhi Dwipayana; Gede Sidi Artajaya (Universitas Udayana, 2018)
This study examines forms of feudalistic ideological hegemony and character resistance against them in literary works set against Balinese sociocultural. This research has a theoretical contribution to the development of science especially about sociological discourse in literature. This study uses a critical descriptive qualitative research design that moves from a functional approach to literary works with Balinese sociocultural background. The primary data sources in this study were the novels of Tarian Bumi (2007) by Oka Rusmini, Incest (2008) by I Wayan Artika, and short story Ketika Kentongan Dipukul di Bale Banjar (1969) by Rasta Sindhu. The study concludes that the feudalistic ideological hegemony in Balinese sociocultural literary works are represented by customary matters of adat and the caste system. The characters resistance against them are carried out in various ways ranging from being strong, independent, showing mimicry attitude; masculinity and sexual disorientation, and being reactionary.